CO2/N2-Responsive Nanoparticles for Enhanced Oil Recovery During CO2 Flooding - Lai, Nanjun; Zhu, Qingru; Qiao, Dongyu; Chen, Ke; Wang, Dongdong; Tang, Lei; Chen, Gang (Frontiers in Chemistry, 2020)
During CO2 flooding, serious gas channeling occurs in ultra-low permeability reservoirs due to the high mobility of CO2. The chief end of this work was to research the application of responsive nanoparticles for mobility control to enhance oil recovery. Responsive nanoparticles were developed based on the modification of nano-silica (SiO2) by 3-aminopropyltrimethoxysilane (KH540) via the Eschweiler-Clark reaction. The proof of concept for responsive nanoparticles was investigated by FT-IR, 1H-NMR, TEM, DLS, CO2/N2 response, wettability, plugging performance, and core flooding experiments. The results indicated that responsive nanoparticles exhibited a good response to control nanoparticle dispersity due to electrostatic interaction. Subsequently, responsive nanoparticles showed a better plugging capacity of 93.3% to control CO2 mobility, and more than 26% of the original oil was recovered. Moreover, the proposed responsive nanoparticles could revert oil-wet surfaces to water-wet, depending on surface adsorption to remove the oil from the surface of the rocks. The results of this work indicated that responsive nanoparticles might have potential applications for improved oil recovery in ultra-low permeability reservoirs.